THE PARENTING TRAINING MODEL BASED ON SPIRITUAL INTELLEGENCE TO IMPROVE THE MOTHER TO CHILD CARE IN THE FAMILY - Asni Ilham (JOURNAL OF EDUCATION SCIENCE, 2015)
The main problem of this research is the low level of maternal care in the family. This is probably caused by the limited frequencies of the maternal participation in the parenting training programs. In response tothis phenomenonrequired anefforttoempowerthemotherby giving themthe knowledgeandskills necessaryto implementgood parenting. Womenempowermentprogramimplementedthroughtraining. Inthisstudywillbe implemented the parenting training model based on spiritual intelligence, which isalleged to be effectiveforimprovingmother’s behavior infamily child care. The theoretical foundation of this research is the concept of parenting training model, adult education concept, the child family care, the spiritual intelligence concept, and the concept of early childhood education.The method that usedinthis studywasa quasi-experimental. The designisthe design(pretest -posttest) agroup(the one grouppretest-posttest design). Groups ofsubjectsweremothersof young childreninearly childhoodAlmourkyGorontalodistrict, amounting to 30 people. The techniques of data collection were using tests, interviews, questionnaires, observation, and documentation study. The analysis technique that usedtotest thehypothesesisthe analysis ofparametricstatisticaldifference test. This testwilllook atdifferent groups ofmothersbeforeand after thetrainingconducted. The statistical test used the two side t test with correlated samplesThe results ofdata processingshowthatthe parentingtraining model based on spiritual intelligence was effectiveforimprovingmother’s behaviorinfamily child care. This is evidenced bytheresults of testingthe hypothesis thatthere is asignificant differencebothtoaspects of knowledge, skills, attitudesandmothers behavior infamily child carebeforeandafter the training.The findings of this research show that the parenting training model based on spiritual intelligence effectively helped to improve the knowledge, skills and attitudes of mothers, hence of impact on improving maternal childcare in the family. Keywords: Child-Care, Spiritual Intelligence, and Parenting Training Model